DESAIN PENAMPUNG AIR HUJAN SEBAGAI PEMANFAATAN AIR HUJAN UNTUK SUMBER AIR CADANGAN BAGI BANGUNAN RUSUNAWA (STUDI KASUS : RUSUNAWA KYAI MOJO JEPARA) (Science and Technology (SciTech), 2022)
One of the essential daily needs of living things in this world that cannot be separated is air. To meet their daily needs, each person needs approximately 75 liters of air. Indonesia is a country located on the equator which has a tropical climate and high rainfall. Even so, most parts of Indonesia still experience water shortages during the dry season and in Rusunawa Kyai Mojo Jobokuto Jepara also experiencing air difficulties, the air difficulty has been going on since last October 2019. This research then aims to take advantage of the rainwater that falls in the flat building to be used as an air standard that will help meet the water needs of its inhabitants. This research will take into account the dimensions of the Rainwater Resevoir (PAH) according to the calculation of the air balance, and also take into account the value of the air requirements of the occupants to match the air that will be accommodated. This research will also consider the Budged Plan (RAB) value in the construction of the rainwater reservoir. And the result for daily water needs is obtained a value of 39.6 m3 / day. The rainwater supply that can be harvested is 261.10 m3 / month. For the container dimensions of 280 m3. And for the Budged Plan (RAB) of IDR 340,599,000Rainwater Storage Design as Rainwater Utilization for Reserve Water Sources for Rusunawa Buildings (Case Study : Rusunawa Kyai Mojo Jepara)